Quality of soybean seeds under application of herbicides or growth regulators - Marchi, Caroline Santana; Paiola Albrecht, Alfredo; Albrecht, Leandro Paiola; Novakoski, Fabiula Patricia; Silva, André Felipe Moreira; Mundt, Tamara Thaís [UNESP] (Revista Brasileira de Ciencias Agrarias, 2021)
Seeds may undergo interference from chemical products that are applied to the mother-plant, either impairing or improving their features, and to determine if there was interference in the seeds, germination and vigor tests are carried out. This study aimed to assess the quality of soybean seeds subjected to pre- and post-emergence herbicides and post-emergence growth regulators. At experiment 1, pre-emergence soybean herbicides were applied, and seeds were sown at the same day of application, at experiment 2, herbicides and growth regulators were applied at post-emergence soybean (V4). Seeds were harvested and subjected to the necessary tests, namely 1,000-seed weight, moisture content, germination, seedling length, tetrazolium and electrical conductivity. In general, herbicides and growth regulators did not cause an adverse impact on soybean seeds quality. Application of flumioxazin or mepiquat chloride caused minimal effects on the soybean seeds quality, with minor reductions in vigor, and no effect on germination.
Qualidade de sementes de soja sob aplicação de herbicidas ou reguladores de crescimento
Keywords: Glycine max L; Physiological quality; Viability; Vigor